The effect of store image on store loyalty and the influence of service quality among leading portuguese retailers - Almeida, Helena Beatriz Moura de (2020)
Nowadays, we live in a society deeply characterized by consumption. In order to adapt to this situation businessmen, especially retailers, had to come up with ever increasingly innovative and appealing strategies to engage consumers. Competition is fierce and only the best can, indubitably, increase their market share. With this study it is intended to sum up the most relevant factors for the consumer in the moment of purchase, in order to respond to the widest range of demands from the market. Therefore, the Butcher’s market was chosen to be analyzed, since meat is one of the cornerstones of any bundle of goods that Portuguese families purchase. This would make these factors overarching to other categories. With this dissertation it is indented to determine what most contributes to increase the loyalty of consumers to a certain store. In order to do that, the two biggest supermarket chains were compared (Pingo Doce and Continente), since both of them comprehend 44% of the market share, which for the scope of this study, is a big enough sample.